2007
DOI: 10.1016/j.bbamem.2006.09.019
|View full text |Cite
|
Sign up to set email alerts
|

The G protein-coupled receptor kinase (GRK) interactome: Role of GRKs in GPCR regulation and signaling

Abstract: G protein-coupled receptor kinases (GRKs) and arrestins are key participants in the canonical pathways leading to phosphorylation-dependent GPCR desensitization, endocytosis, intracellular trafficking and resensitization as well as in the modulation of important intracellular signaling cascades by GPCR. Novel studies have revealed a phosphorylation-independent desensitization mechanism operating through their RGS-homology (RH) domain and the recent determination of the crystal structures of GRK2 and GRK6 has u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
309
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 365 publications
(317 citation statements)
references
References 70 publications
7
309
0
1
Order By: Relevance
“…Interestingly, in addition to its reported alteration in cardiovascular and inflammatory pathologies (3,10), emerging data indicate changes in GRK2 expression in certain tumors (11). The fact that general but not cardiac-specific GRK2 knockout mice are embryonic lethal (12) further supports the notion that this protein could play a central, general role in key cellular processes as proliferation or migration.…”
mentioning
confidence: 70%
“…Interestingly, in addition to its reported alteration in cardiovascular and inflammatory pathologies (3,10), emerging data indicate changes in GRK2 expression in certain tumors (11). The fact that general but not cardiac-specific GRK2 knockout mice are embryonic lethal (12) further supports the notion that this protein could play a central, general role in key cellular processes as proliferation or migration.…”
mentioning
confidence: 70%
“…In vitro studies have also shown the ability of G␣ q to simultaneously bind to both PLC␤ and phosphatidylinositol 3-kinase (43). Our preliminary data indicate that both G␣ q /PKC and G␣ q /MEK5 association are inhibited in the presence of the GRK2 RH domain, 4 which has been reported to interact with G␣ q and block the interaction with its effector PLC␤ (21,44,45). However, the G␣ q sites required for the interactions with both PKC and MEK5 appear to be different from those involved in PLC␤ binding because a G␣ q mutant that is unable to interact with the latter promotes ERK5 activation and readily associates to PKC.…”
Section: Discussionmentioning
confidence: 99%
“…GRK3 (or β-adrenergic receptor kinase 2) belongs to a subfamily of kinases called GRKs (26)(27)(28). GRK3 is best known to phosphorylate the agonist-occupied form of β-adrenergic receptors, leading to desensitization of the receptors to their agonists (29,30).…”
Section: Discussionmentioning
confidence: 99%